2017
DOI: 10.1155/2017/7183516
|View full text |Cite
|
Sign up to set email alerts
|

PEDF Is Associated with the Termination of Chondrocyte Phenotype and Catabolism of Cartilage Tissue

Abstract: Objective. To investigate the expression and target genes of pigment epithelium-derived factor (PEDF) in cartilage and chondrocytes, respectively. Methods. We analyzed the expression pattern of PEDF in different human cartilaginous tissues including articular cartilage, osteophytic cartilage, and fetal epiphyseal and growth plate cartilage, by immunohistochemistry and quantitative real-time (qRT) PCR. Transcriptome analysis after stimulation of human articular chondrocytes with rhPEDF was performed by RNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Conversely, downregulated signaling pathways among Wisp1 -/cells included several pathways that negatively regulate chondrogenesis or promote cartilage matrix degradation, such as AMP-activated protein kinase (AMPK) signaling (Z score = -0.447) (36) and pigment epithelium-derived factor (PEDF) signaling (Z score = -0.447) (Supplemental Table 5) (37). Pathways with no change between Wisp1 +/+ and Wisp1 -/cells are shown in Supplemental Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, downregulated signaling pathways among Wisp1 -/cells included several pathways that negatively regulate chondrogenesis or promote cartilage matrix degradation, such as AMP-activated protein kinase (AMPK) signaling (Z score = -0.447) (36) and pigment epithelium-derived factor (PEDF) signaling (Z score = -0.447) (Supplemental Table 5) (37). Pathways with no change between Wisp1 +/+ and Wisp1 -/cells are shown in Supplemental Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SerpinF1 has been reported to be increased in OA cartilage [45], and a recent study demonstrated that SerpinF1 deficiency reduces cartilage damage in an age-dependent manner in the murine monoiodoacetamide OA model, and overexpression in chondrocytes enhances cytokine-induced expression of catabolic MMPs [67]. In support of these observations, a different study demonstrated that stimulation of chondrocytes with recombinant SERPINF1 led to a catabolic phenotype and chondrocyte terminal differentiation [68].…”
Section: Clade Fpigment Derived Epithelial Factor and Alpha-2 Antiplasminmentioning
confidence: 88%
“…Pigment epithelium derived factor (PEDF) is the product of the EPC1 gene and is known to be anti-angiogenic. Previously PEDF has been shown to be preferentially expressed in OA cartilage contributing to OA pathogenesis by upregulating matrix degrading factors (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Pigment epithelium derived factor (PEDF) is the product of the EPC1 gene and is known to be anti-angiogenic. Previously PEDF has been shown to be preferentially expressed in OA cartilage contributing to OA pathogenesis by upregulating matrix degrading factors (38, 39). Whilst there was evidence of an association between rs34656141 with eQTL expression for AP3D1, DOT1L and AMH in fibroblasts these signals did not colocalise.…”
Section: Discussionmentioning
confidence: 99%